STAGING OF THE BRAND STYLE FORMATION BY THE EXAMPLE OF FASHION HOUSE LOUIS VUITTON - Ніколаєва, Т. В.; Гайова, І. Л.; Давиденко, І. В.; Баранова, А. І.; Паранько, Н. П. (Art and Design, 2021)
The purpose. To study the historical experience of creating brand products on the example of the formation and development of the Louis Vuitton fashion house. Methodology. The work uses methods of literary-analytical and system-historiographic analysis. To study the object of research and the factors that most influence its development a critical analysis of scientific and popular publications has been applied, materials on the history of the formation of the brand’s style have been analyzed, the prerequisites for the emergence of the graphic style of Louis Vuitton have been researched, as an example of identifying fashion products using a set of iconic identification elements. Results. At each stage of the formation of the Louis Vuitton fashion house style, the main features of the brand are preserved, expressing the idea of product conformity to a certain market segment. At the same time, the main elements of the brand symbols are in constant development, in accordance with the marketing policy and fashion trends, ensuring the relevance of Louis Vuitton products for many decades. Today, the trend of identifying fashion products with human status is becoming an thoroughly planned process. The challenge of modern design is to cover the widest range of consumer needs, looking back at the history and focusing its efforts on the future models. Scientific novelty lies in the reviewing of innovation stages in the formation of brand products design, as a separate activity area. Practical significance. The determined principles of working on the creation of brand products can be used in the educational process for training of future designers.